Peculiarities of Perception of Teaching Style and Motivation of Students’ Learning - Romanovskyi, O. G.; Reznik, S. M.; Chebakova, Yu. G. (Wydawnictwo Adam Marszałek, 2019)
The objective of the article is to study the peculiarities of students’ perception of teaching style and to determine the correlation between such perception and motivation of students’ learning. The group of respondents included 254 future social and 156 technical specialists (a total of 410 students), methods of research were questioning and testing; Pearson correlation coefficient was used for statistical analysis. Students perceived the democratic teaching style as the most positive, and its use is associated with educational and cognitive motives. Authoritarian and laissez faire styles are seen as undesirable. The first is related to the motives of avoidance, and the second has feedback from professional motives of students. Comparison of the results of the survey of future social and technical specialists allowed us to determine that the latter perceive the authoritarian style more positively than students of social specializations.
Keywords: teacher leadership style; style of pedagogical communication; motivation of student learning